Nerve-Driven Immunity Neurotransmitters and Neuropeptides in the Immune System - Levite, Mia.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2012)
“Nerve-Driven Immunity: Neurotransmitters and Neuropeptides in the Immune System” summarizes, analyzes and sheds new light on an unrecognized, yet very important role of key neurotransmitters and neuropeptides in the immune system. Each chapter of the book deals with a different neurotransmitter/neuropeptide from the following list: Dopamine, Adrenaline, Noradrenaline, Acetylcholine, Glutamate, GABA, Somatostatin, Neuropeptide Y (NPY), Vasoactive intestinal polypeptide (VIP), Calcitonin gene related peptide (CGRP), Opioids and Cannabinoids. For each of these neurotransmitters/neuropeptides, the following four topics are discussed: The specific receptors for the neurotransmitter/neuropeptide expressed in various types of immune cells The direct effects induced by the neurotransmitter/neuropeptide in various types of immune cells (either resting or activated), and the specific immune functions and features it activates/elevates or rather inhibits in specific concentrations The production of the neurotransmitter/neuropeptide in, and its release by, various types of immune cells The involvement of the neurotransmitter/neuropeptide in various diseases of the immune system (among them autoimmune diseases, immunodeficiency diseases and hematological cancers) The book includes many original figures, overview tables, and proposed models of events which are instrumental, enriching and stimulating for the reader. In light of the above-mentioned aspects, “Nerve-Driven Immunity: Neurotransmitters and Neuropeptides in the Immune System” is ideally suited as a textbook for new courses in Immunology, Neurology, Neuro-immunology or Pharmacology. The book chapters were written by highly skilled authors from 10 countries: the USA, the United Kingdom, Italy, Israel, Sweden, France, Germany, Spain, Serbia and Romania. “Nerve-Driven Immunity” is a term first coined by Dr. Mia Levite (the editor of the book).
Mia Levite: Dopamine in the immune system: Dopamine receptors in immune cells, potent effects, endogenous production and involvement in immune and neuropsychiatric diseases -- Marco Cosentino and Franca Marino: Nerve driven immunity - Noradrenaline and adrenalina -- Eran Nizri and Talma Brenner: Acetylcholine and Cholinergic modulation of immune responses -- Yonatan Ganor and Mia Levite: Glutamate in the immune system: glutamate receptors in immune cells, potent effects, endogenous production and involvement in disease -- Zhe Jin, Suresh Kumar Mendu, Amol Bhandage and Bryndis Birnir: GABA is an effective immunomodulatory molecule in the brain and in the periphery -- Jana Ninković and Sabita Roy: The Effects of Opioids on Immune Cells, Functions and Diseases -- Toomas Talme and Karl-Gösta Sundqvist: The effects of Somatostatin on immune cells, functions and diseases -- Mirjana Dimitrijević and Stanislava Stanojević: Neuropeptide Y – the story, the players, the outcomes -- Mario Delgado and Doina Ganea: Vasoactive Intestinal Peptide: Immune mediator and potential therapeutic agent -- Bernhard Holzmann: Nerve-driven immunity - The effects of neurotransmitters on immune cells, functions and disease. CGRP -- Radu Tanasescu and Cris S. Constantinescu: The effects of Cannabinoids on immune cells, responses and diseases.
Keywords: Immunology; Neurochemistry; Neurosciences; Immunology; Neurochemistry; Neurosciences